THE IMPACT OF THE EXTERNAL AUDITOR'S PROCEDURES ACCORDING TO INTERNATIONAL AUDITING STANDARDS (320, 330) IN REDUCING SIGNIFICANT MISREPRESENTATIONS OF THE FINANCIAL STATEMENTS - Ali Lateef Ayyed Alghezi; Sarah Abdulameer Kamil Abugallal; Majid Gazi Hasan; Waad Hadi Abd (American Journals, 2023)
The research aims to know the procedures of the external auditor in accordance with the International Auditing Standard (320, 330) that enable him to express his opinion on the financial statements that they are generally prepared correctly, honestly and free from material distortions, and the most important of these procedures have been addressed in the theoretical framework of the research And to the most important reasons that lead to the existence of material misstatements in the financial statements, and then preparing a questionnaire targeting workers in the field of control and auditing according to a sample of (127), with which the study reached the most important conclusions, and the risks of significant misstatements in the financial statements increase when the external auditor does not separate between each of The error is unintentional and the fraud resulting from the management. The latter is preoccupied with detecting minor errors, and to the most important recommendations, which is the need to use Relative importance when planning the audit process and during the examination stage in separating between unintentional error and fraud resulting from management and not being preoccupied with detecting minor errors, which is the focus on detecting misrepresentation material in the financial statements.
Keywords: External auditor procedures. Material Misstatements of Financial Statements, International Standards on Auditing (320, 330).